A new cryptic species of the genus Eleutherodactylus (Amphibia: Anura: Eleutherodactylidae) from Cuba - Díaz, Luis M.; Hedges, S. Blair; Schmid, Michael (Zootaxa, 2012)
The widely distributed grass frog of Cuba, Eleutherodactylus varleyi, is shown here to comprise two species. One, E. var-leyi, occurs in western and central Cuba while the other, E. feichtingeri n. sp., occurs in central and eastern Cuba. The twospecies are sympatric in central Cuba, and syntopic in the vicinity of Sierra de Cubitas, Camagüey Province. A molecularphylogeny of mitochondrial DNA sequences from 18 localities confirms the existence of two well-supported major cladescorresponding to each of these species, and the sympatry of the species. Tympanum size and advertisement call are themost useful diagnostic characters, although the two species are shown to have karyotypic differences as well. Possible character displacement in morphology and vocalization, in the area of sympatry, is discussed.